Hepatocellular carcinoma may display elevated nestin expression in endothelial cells: experimental study - Nogueira, Adriano Barreto; Nogueira, Ariel Barreto; Costa, Anderson Lino Costa; Lima, Fabiana Roberto; Siqueira, Sheila Aparecida; Teixeira, Manoel Jacobsen (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Nestin, a class VI intermediate filament protein, is highly expressed in the portal mesenchyme and sinusoidal endothelium of the human fetal liver, but scarcely expressed in adult portal vessel endothelium. During experimental liver regeneration, an increased number of nestin-positive parenchymal cells have been observed in the zone adjacent to the Hering canals. These parenchymal cells are regarded as hepatic stem cells or hepatoblasts, which may be involved in hepatocellular carcinogene-sis. In the light of recent reports describing nestin-positive parenchymal cells in hepatocellular carcinoma, we aimed to use this tumor type as a positive control for immunohistochemical detection of nestin. DESIGN AND SETTING: Experimental study conducted at a university hospital. METHODS: Hepatocellular carcinoma sections from one case were analyzed for nestin expression by im-munohistochemistry using confocal microscopy. RESULTS: Surprisingly, a conspicuous pattern resembling liver sinusoid-like cytoarchitecture was ob-served upon nestin staining of endothelial cells. CONCLUSIONS: This pattern has not been previously described. The preliminary results shown here sug-gest that nestin-positive endothelial cells are located in niches of immature or proliferative cells. Moreover, nestin expression in endothelial cells of hepatocellular carcinoma enhances the role of angiogenesis in this tumor type, although the prevalence of this immunohistopathological pattern remains to be deter-mined. Finally, hepatocellular carcinoma is an effective positive control for nestin staining in fluorescent immunohistochemistry.